2016
DOI: 10.1136/bmj.i4823
|View full text |Cite
|
Sign up to set email alerts
|

Risk of erectile dysfunction associated with use of 5-α reductase inhibitors for benign prostatic hyperplasia or alopecia: population based studies using the Clinical Practice Research Datalink

Abstract: ObjeCtiveTo estimate the risk of erectile dysfunction in men who used 5-α reductase inhibitors to treat benign prostatic hyperplasia or alopecia. DesignCohort studies with nested case-control analyses. POPulatiOnTwo populations of men free of risk factors for erectile dysfunction and other sexual dysfunction or its treatment: men aged 40 or more with benign prostatic hyperplasia who received a prescription for a 5-α reductase inhibitor (finasteride or dutasteride) or α blocker, or both, and men aged 18-59 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…A meta-analysis of clinical trials in men with prostatic hyperplasia found that the risk of ED was significantly increased with combined 5α-RI plus α 2 adrenergic receptor blocker compared to α 2 adrenergic receptor blocker alone (Favilla et al, 2016). However, an observational study found that the risk of ED was not increased with combined 5α-RI plus α 2 adrenergic receptor blocker compared to α 2 adrenergic receptor blocker alone (Hagberg et al, 2016). A case-control study found that sexual and erectile function of men exposed to finasteride 1 mg daily did not differ from controls (Tosti, Piraccini & Soli, 2001), and an observational study found that sexual function in men did not decline over the first 4–6 months of exposure to finasteride 1 mg (Tosti et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of clinical trials in men with prostatic hyperplasia found that the risk of ED was significantly increased with combined 5α-RI plus α 2 adrenergic receptor blocker compared to α 2 adrenergic receptor blocker alone (Favilla et al, 2016). However, an observational study found that the risk of ED was not increased with combined 5α-RI plus α 2 adrenergic receptor blocker compared to α 2 adrenergic receptor blocker alone (Hagberg et al, 2016). A case-control study found that sexual and erectile function of men exposed to finasteride 1 mg daily did not differ from controls (Tosti, Piraccini & Soli, 2001), and an observational study found that sexual function in men did not decline over the first 4–6 months of exposure to finasteride 1 mg (Tosti et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…To identify men with first‐time (incident) antidepressant‐treated depression after treatment with a study drug, we excluded men with a diagnosis of depression or suicidal behaviors (ideation or attempts), or men who received prescriptions for antidepressant medications prior to cohort entry. These methods were described in more detail in a prior publication …”
Section: Methodsmentioning
confidence: 99%
“…These results add to the possibility of a connection between sexual dysfunction and 5αRI use (for any age) although alternative explanations such as a nocebo effect and duration of BPH are contributors. It has been suggested that in trials where dutasteride is indicated for BPH, it is the duration of disease that increases the risk for sexual dysfunction versus finasteride or dutasteride used to treat the condition . There is also evidence that presenting the possibility of sexual dysfunction with 5αRI use to patients increases incidences even with placebo use, establishing the presence of a nocebo or psychologically induced detrimental effect .…”
Section: Discussionmentioning
confidence: 99%